2004
DOI: 10.1046/j.1365-2419.2003.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of freshwater input and wind on landings of anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus) in shelf waters surrounding the Ebre (Ebro) River delta (north‐western Mediterranean)

Abstract: Time series analyses (Box–Jenkins models) were used to study the influence of river runoff and wind mixing index on the productivity of the two most abundant species of small pelagic fish exploited in waters surrounding the Ebre (Ebro) River continental shelf (north‐western Mediterranean): anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus). River flow and wind were selected because they are known to enhance fertilization and local planktonic production, thus being crucial for the survival of fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
155
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 38 publications
6
155
0
2
Order By: Relevance
“…Bayesian models have proven their value for assessing the underlying stock-recruitment relationship of exploited species, along with the associated uncertainty (Dorn, 2002;Mäntyniemi and Romakkaniemi, 2002;Michielsens and McAllister, 2004). In many stocks and particularly in small pelagic fish, the sensitivity of recruitment to the environment impedes the use of traditional stock-recruitment relationships (e.g., Ricker or Beverton-Holt curves) as the unique driver of Figure 2 Posterior distributions (solid lines) for the parameters of the model used to incorporate an environmentally forced recruitment of European anchovy (Engraulis encrasicolus) in the Gulf of Cádiz, Spain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bayesian models have proven their value for assessing the underlying stock-recruitment relationship of exploited species, along with the associated uncertainty (Dorn, 2002;Mäntyniemi and Romakkaniemi, 2002;Michielsens and McAllister, 2004). In many stocks and particularly in small pelagic fish, the sensitivity of recruitment to the environment impedes the use of traditional stock-recruitment relationships (e.g., Ricker or Beverton-Holt curves) as the unique driver of Figure 2 Posterior distributions (solid lines) for the parameters of the model used to incorporate an environmentally forced recruitment of European anchovy (Engraulis encrasicolus) in the Gulf of Cádiz, Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit the small RMSE for observed and estimated catches (5 million corresponding to 3.84% of the maximum value of observed catches) can be a consequence of the process simplification induced by the assumption of constant fishing-induced mortality, it shows the goodness of fit of the model in a plausible "What if" scenario: What if catches are proportional to the population, and that scenario is not far from reality according to the results from the previously developed Bayesian model. Although a proportionality between catches and abundance is not necessarily observed and is the subject of hot debate (Pauly et al, 2013), this proportionality is frequently observed in short-lived small pelagic fish (Lloret et al, 2004). The dual resolution also facilitates the embedding of environmental forcing into generalist models, such as the GPDM for fishery management (Mäntyniemi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations